Creating Awareness on Local Foods to Enhance Dietary Diversity among Poor Households in Balanga LGA, Gombe State - Onyekachi, Mabel; Clement Bala, Ezekiel; Dida, Joyce; Abubakar, Jatau; Olumuyiwa, Babaranti; Loko, Ekundayo; Mahmood, Abubakar; Garba, Ibrahim; Kuma, Lanem Law; Adeniyi, Kehinde; Solanke, Ojuolape; Oluwafunmilola Olotu, Joan (Kashere Journal of Politics and International Relations, 2025)
Malnutrition remains a critical public health challenge in Nigeria, particularly among poor households in rural areas such as Balanga Local Government Area in Gombe State. Despite the region’s agricultural potential, many families suffer from inadequate dietary diversity, micronutrient deficiencies, and high rates of child stunting and wasting. This study examines the effectiveness of the National Social Safety Nets Project-Accelerating Nutrition Results in Nigeria initiative in improving nutritional awareness through food demonstrations using locally available foods. The research hypothesizes that leveraging indigenous food resources can enhance dietary diversity and reduce malnutrition among vulnerable households. A purposive sampling technique was employed, targeting 3,681 beneficiary households across 215 communities in Balanga LGA. Cash Transfer Facilitators and community volunteers were trained to conduct food demonstrations, emphasizing the nutritional benefits of locally accessible foods such as moringa, cowpeas, and baobab leaves. The intervention also included coaching and mentorship to reinforce dietary practices. Results indicate widespread participation, with 84 community volunteers providing follow-up mentorship to reinforce learning. The study highlights the awareness of the potential of locally sourced foods in addressing malnutrition, particularly in resource-limited settings. By promoting indigenous food utilization, households can improve dietary diversity without relying on costly external interventions. The findings underscore the need for community-centered nutrition programs that integrate education, local food systems, and sustainable agricultural practices. Recommendations include scaling up similar initiatives, strengthening policy support for local food utilization, and enhancing community engagement to ensure long-term nutritional improvements.